FRAMEWORK OF ELECTRONIC HEALTH RECORDS’ TREND ANALYSIS USING INTER, INTRA AND MULTI ASSOCIATIONS RULE MINING - KAREEM, SABA (2019)
Digitalization of healthcare records in the form of Electronic Health Records (EHR) has attracted many stakeholders to focus on utilizing the data for better understanding and improvement of the healthcare industry